2017
DOI: 10.1038/onc.2017.81
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational modification of HINT1 mediates activation of MITF transcriptional activity in human melanoma cells

Abstract: Microphthalmia transcription factor (MITF) is a basic helix-loop-helix leucine zipper (bHLH-Zip) DNA-binding protein. This transcription factor plays a crucial role in the physiological and pathological functions of distinct cell types. MITF transcriptional activity is inhibited by the histidine triad nucleotide-binding protein 1 (HINT1) through direct binding. We previously reported that this association is disrupted by the binding of the second messenger ApA to HINT1. ApA is mainly produced in the mammalian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 37 publications
0
42
0
Order By: Relevance
“…In addition to the cofactors outlined above, MITF also interacts with histidine triad nucleotide-binding protein 1 (HINT1/PKCI) (Razin et al 1999). Although the interaction has been best-characterized in mast cells, it also occurs in melanoma (Motzik et al 2017). Transcription activation by MITF is inhibited by its direct interaction with HINT1 that can be diminished by activation of the KIT RTK in melanoma cells or FC receptor epsilon on mast cells.…”
Section: Mitf Cofactorsmentioning
confidence: 99%
“…In addition to the cofactors outlined above, MITF also interacts with histidine triad nucleotide-binding protein 1 (HINT1/PKCI) (Razin et al 1999). Although the interaction has been best-characterized in mast cells, it also occurs in melanoma (Motzik et al 2017). Transcription activation by MITF is inhibited by its direct interaction with HINT1 that can be diminished by activation of the KIT RTK in melanoma cells or FC receptor epsilon on mast cells.…”
Section: Mitf Cofactorsmentioning
confidence: 99%
“…Several studies have revealed that aminoacyl-tRNAs function to transfer amino acids to ribosomes during protein synthesis; therefore, the increased protein synthesis rate of cancer cells indicates that the level of aminoacyl-tRNA in cancer tissues is significantly higher than in normal tissue. [23][24][25] In this study, levels of following metabolites related to the aminoacyl-tRNA biosynthesis in cancer were altered: L-alanine, L-arginine, and Lasparagine. These differential metabolites in lung adenocarcinoma tissue affect the synthesis of aminoacyl-tRNA biosynthesis, which affect protein synthesis and further regulate tumor cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…NUDIX homology domains (NHD) in enzymes and the Nudix type 2 gene product, Ap4A hydrolase, have been shown responsible for Ap4A degradation. The human fragile histidine triad (FHIT) is a tumor suppressor, whose Ap4A hydrolase activity is not required for antioncogene activity, while Ap4A binding has a positive effect [42][43][44][45][46][47]. The Microphthalmia transcription factor (MITF) is a basic helix-loop-helix leucine zipper (bHLH-Zip) DNA-binding protein.…”
Section: Ap4a and Oligoadenylatesmentioning
confidence: 99%
“…MITF transcriptional activity is inhibited by the histidine triad nucleotide-binding protein 1 (HINT1) through direct binding. The association is disrupted by the binding of Ap4A to HINT1 [44].…”
Section: Ap4a and Oligoadenylatesmentioning
confidence: 99%